The trope of home and the representation of Muslim women in Rokeya Sakhawat Hossain and in Attia Hosain's Sunlight on a Broken Column - Hasan, Md. Mahmudul (A P H Publishing Corporation, 2007)
The trope of home has received a perennial interest in both the writings of colonialist writers and in the works of those from colonised society. Whereas the colonialists are keen on expanding their “home” in foreign territories, the colonised remain culturally dislocated in their own homeland and engage in ideological debates to regain it. In the patriarchal discourse, women are relegated to the private world of home and family. In recent feminist theory, women, especially from subaltern societies, seek for a space to have a sense of belonging. The issue of multiple meanings of home and of multiple modes of homelessness finds symbolic representation in Rokeya’s feminist works and in Attia’s Sunlight on a Broken Column (1961). In the light of their treatment of the trope of home, this paper touches upon its re-readings in the feminist ideology of “being home and non-being home”(Martin & Mohanty, 1988, p.196). Occasional references are made to Woolf’s A Room of One’s Own (1929), which also deals with women’s longing for home and for belongingness. I propose to subvert the binarism of private and public, and of male and female associated with the received notion of the home. The homelessness of the colonised because of colonial dispossession, and women’s homeless condition because of their gender orientation constitute the central thesis of this paper. Whereas the gendered, domestic norms of izzat (honour) and sharum (modesty) restrict women’s independence and impede their individual fulfilment, colonial structures and education policy render the colonised culturally dislocated and spiritually homeless. In this regard, I endorse Sahgal’s (1993) assertion that “[…] migration can take place without even leaving one’s soil” (p.119). Even after the decolonisation, the legacy of the colonial cultural and education policy continues to culturally displace indigenous peoples. It has created an ambivalence among the colonised of adopting western value systems (especially “individualism”) and preserving their cultural rootedness. This difficult predicament is a palpable consequence of colonialism.